2007
DOI: 10.1002/cbic.200700044
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of the Membrane‐Proximal Region of Herpes Simplex Virus Type 1 Glycoprotein H in Membrane Fusion and Virus Inhibition

Abstract: We have identified a putative membrane-interacting domain preceding the transmembrane domain of the Herpes simplex virus type 1 (HSV-1) glycoprotein H (gH). Peptides derived from this region interact strongly with membranes and show a high tendency to partition at the interface. This region is predicted to bind at the membrane interface by adopting an alpha helical structure. Peptides representing either the HSV-1 gH pretransmembrane region or a scrambled control with a different hydrophobic profile at the poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 57 publications
3
57
0
Order By: Relevance
“…HSV-1 infection, similarly to other enveloped viruses, is achieved through fusion of the lipid bilayer of the viral envelope with a host cell membrane. The core fusion machinery of herpesviruses is well conserved and consists of the envelope glycoprotein B (gB) and the heterodimeric complex of gH/gL (15)(16)(17)(18)(19)(20). Although numerous studies have indicated that both gB and gH/gL exhibit varying degrees of fusogenic properties, the complete fusion is only achieved when the three proteins act together (21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-1 infection, similarly to other enveloped viruses, is achieved through fusion of the lipid bilayer of the viral envelope with a host cell membrane. The core fusion machinery of herpesviruses is well conserved and consists of the envelope glycoprotein B (gB) and the heterodimeric complex of gH/gL (15)(16)(17)(18)(19)(20). Although numerous studies have indicated that both gB and gH/gL exhibit varying degrees of fusogenic properties, the complete fusion is only achieved when the three proteins act together (21)(22)(23).…”
mentioning
confidence: 99%
“…The three classes of viral membrane fusion proteins have been identified largely on the basis of the key structural features of the proteins, and a comprehensive treatment of this subject can be found in recent reviews (1, 30 -32). Although no structural data for HSV-1 gH or any of its homologues in other herpesviruses are available, gH has also been considered as a likely fusion effector (15,16,19,33).…”
mentioning
confidence: 99%
“…Although the structure of gH/gL is unknown, indirect evidence suggests that this complex also has fusogenic properties. For example, synthetic peptides corresponding to several regions of HSV gH associate with membranes (9). Fusion-compromised HSV gH mutants have been isolated, emphasizing the importance of gH for fusion (10)(11)(12).…”
mentioning
confidence: 99%
“…These regions, in conjunction with the membrane-proximal region (32) and the transmembrane anchor of the protein, seem to form a continuous tract of hydrophobic membrane interacting surfaces that could simultaneously destabilize viral and cellular opposing membranes at the point of fusion. According to recent studies, binding of gD to its receptor is followed by hemifusion carried out by gH/gL, and full fusion is completed by the interaction between gH/gL and gB that concurrently leads to complete bilayer merging (33,34).…”
mentioning
confidence: 99%